2019
DOI: 10.1186/s42269-019-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stress conditions for carotenoids accumulation in Chlamydomonas reinhardtii as added-value algal products

Abstract: Background: Microalgae, the third-generation source of biofuel have invaluable bio-refineries such as carotenoids. The accumulation of carotenoids in the algal cell is based on several parameters during algal growth. Some of these parameters are irradiance and cultivation periods which figures the photoperiod during algal growth. In this work, 0.6 g/L Chlamydomonas reinhardtii, green algae strain, was cultivated using the BG-11 medium in bubble column photobioreactor illuminated by white cool fluorescent 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among different intensities of light, the growth of the test organism increased by 2.58‐fold when illuminated continuously with 60 µE of white light (Figure 5). The green microalga Chlamydomonas reinhardtii cultivated in column photobioreactor illuminated with irradiance of 149 µmol/m 2 /s accumulated maximum amount of carotenoids equivalent to 2.15 g/L biomass [43]. White light is reported to support more growth as it has a range of radiations required for optimal photosynthesis as reported for other microalgae [18,30,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different intensities of light, the growth of the test organism increased by 2.58‐fold when illuminated continuously with 60 µE of white light (Figure 5). The green microalga Chlamydomonas reinhardtii cultivated in column photobioreactor illuminated with irradiance of 149 µmol/m 2 /s accumulated maximum amount of carotenoids equivalent to 2.15 g/L biomass [43]. White light is reported to support more growth as it has a range of radiations required for optimal photosynthesis as reported for other microalgae [18,30,44].…”
Section: Discussionmentioning
confidence: 99%
“…Erdoğan et al [51] reported 0.14% vialoxanthin, 0.24% lutein, 0.015% α‐carotene, and 0.055% β‐carotene in Scenedesmus protuberans . On the contrary, the microalga C. reinhardtii produced 0.85 mg/g astaxanthin, 0.87 mg/g lutein, and 0.64 mg/g β‐carotene [43]. Gong and Bassi [17] reported production rate of 11.98 mg lutein/g dries biomass/day in Chlorella vulgaris UTEX 265 in a photobioreactor.…”
Section: Discussionmentioning
confidence: 99%
“…For this microalga, the response to exposure to different stress in combination with light stress has been widely investigated particularly in association with the induction of carotenoids synthesis [29][30][31][32]. This aspect emerged from the trend of changes of chlorophyll content in the cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of photo-protective responses in an outdoor photobioreactor has already been shown in the strain CC124, which was able to synthesize a considerable content of zeaxanthin during the process of hydrogen production [15]. Although the physiology of C. reinhardtii is well known, the studies carried out for the application of this microalga mainly concerned the improvement of hydrogen production efficiency [25,27], and the changes in the chlorophyll fluorescence for monitoring different kinds of stress, particularly photo-oxidative stress, such as high light exposure and anaerobiosis [28][29][30][31]. Some studies have dealt with the use of its exhausted biomass after H 2 production, as biochar [47].…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose-containing algae can be used as a renewable feedstock for bioethanol production -although algae are generally known for their low cellulose and hemicellulose content, they have enough sugar content to be fermented for bioethanol production (El-Mekkawi et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%